Found - Cast, P. C.; Cast, Kristin (Cast, P. C. House of night, other world, 2021)
"Fog rolls into Tulsa, and with it comes Darkness. Zoey knows something is up, and that the something involves Neferet, but Neferet can't possibly be freed, right? Other Neferet and her companion, Lynette, arrive in Woodward Park to set this world's Neferet free from her grotto prison, and discover there may be those who sympathize with their cause. Meanwhile, Other Kevin and Other Stark are hot on their trail, but how can the new friends travel to this world without invoking Old Magick and paying a costly, perhaps deadly, price? In Found, the culmination of the House of Night Other World series, a surprisingly talented fledgling, an immortal, and the unlikeliest of allies will band together with Zoey and the Nerd Herd. Will they be powerful enough to defeat her old nemesis, or will two worlds be destroyed and claimed by Darkness? Find out in the thrilling conclusion to the House of Night Other World series!"--Back cover